Pengaruh Penggunaan Model Pbl Berbantuan Buku Suplemen Ipas Terhadap Hasil Belajar Kognitif Siswa Kelas IV di SDN 39 Pontianak Kota - Badariyah Badariyah; Hery Kresnadi; Rio Pranata (Departement of Mathematics Education, 2024)
This study aims to analyze effect of using the PBL model assisted by science and science supplement books on cognitive learning outcomes class IV students SDN 39 Pontianak City. The method used experiment the form Quasi-Experimental Design with non-equivalent control group design. The population this study were classes IVA and IVB SDN 39 Pontianak City. The sample for research class IVA with 31 students and class IVB with 32 students. The data collection technique used is measurement technique and the data collection tool is written test the form multiple choice questions. Based data analysis, the average results of final test the experimental class and the average of final test the control class were obtained. The results of hypothesis testing using the Independent Sample T-test obtained tcount=0.191 with significance level of α=5%, obtained ttable=0.05, which means tcount>ttable, then Ha is accepted. This proves that there is influence of using the PBL model assisted IPAS supplement book. Based the results of the effect size calculation, it is obtained that it is 0.546180, which 69%. Thus, can be concluded the PBL model assisted by science and technology supplement books has positive influence on cognitive learning outcomes class IV students SDN 39 Pontianak City.